1950
DOI: 10.1085/jgp.33.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Action Spectra of Marine Algae

Abstract: A polarographic oxygen determination, with tissue in direct contact with a stationary platinum electrode, has been used to measure the photosynthetic response of marine algae. These were exposed to monochromatic light, of equal energy, at some 35 points through the visible spectrum (derived from a monochromator). Ulva and Monostroma (green algae) show action spectra which correspond very closely to their absorption spectra. Coilodesme (a brown alga) shows almost as good correspondence, including the spectral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
1
3

Year Published

1959
1959
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 381 publications
(161 citation statements)
references
References 2 publications
7
150
1
3
Order By: Relevance
“…(From Haxo 2008, unpublished manuscript. ) The single most cited (293 times) of Blinks's many photosynthesis papers is that by Haxo and Blinks (1950) on red algae, which has been recognized by a wide variety of photosynthesis investigators in more than 36 reviews on photosynthesis and more than 200 published articles (not including the many textbooks on plant physiology that quote him) (ISI Web of Knowledge). A series of important evaluations of this work and that of Blinks in photosynthesis are given below.…”
Section: Haxo Continuedmentioning
confidence: 99%
See 4 more Smart Citations
“…(From Haxo 2008, unpublished manuscript. ) The single most cited (293 times) of Blinks's many photosynthesis papers is that by Haxo and Blinks (1950) on red algae, which has been recognized by a wide variety of photosynthesis investigators in more than 36 reviews on photosynthesis and more than 200 published articles (not including the many textbooks on plant physiology that quote him) (ISI Web of Knowledge). A series of important evaluations of this work and that of Blinks in photosynthesis are given below.…”
Section: Haxo Continuedmentioning
confidence: 99%
“…It is widely acknowledged that the modern era was introduced by the work of Haxo and Blinks (1950). The latter workers showed that in red algae (Rhodophyta) the biliproteins acted largely as the lightharvesting pigment replacing chlorophyll in this role.…”
Section: Larkum and Weyrauch (1977) Also Statedmentioning
confidence: 99%
See 3 more Smart Citations